GE_GERICHTE P/4818/2024 vom 21. November 2024 - GE Cour de justice (2024)
RUPTURE DE BAN;VIOLENCE CONTRE LES AUTORITÉS;EXPULSION(DROIT PÉNAL);CONCOURS D'INFRACTIONS | CP.291; CP.285; LStup.19a; CP.66abis